



 
Hi Hugh, Suppose the expression was $5y + 5 = 2y$ and you were asked to solve for $y.$ If this were true then my first step would be to add $2y$ to each side to obtain \[5y + 5  2y = 2y  2y \mbox{ which simplifies to } 5y  2y + 5 = 0.\] Next adding $5$ to each side and simplifying I get \[(5  2)y = 5.\] Finally multiplying both sides by $\large \frac{1}{5  2}$ and again simplifying I get \[y = \frac{5}{5  2}= \frac{5}{3}.\] Try this same approach with the original expression $xy + x = y.$ Write back if you need more assistance,  


Math Central is supported by the University of Regina and the Imperial Oil Foundation. 